2022
DOI: 10.3390/ijms23031522
|View full text |Cite
|
Sign up to set email alerts
|

Induction of PLXNA4 Gene during Neural Differentiation in Human Umbilical-Cord-Derived Mesenchymal Stem Cells by Low-Intensity Sub-Sonic Vibration

Abstract: Human umbilical-cord-derived mesenchymal stem cells (hUC-MSC) are a type of mesenchymal stem cells and are more primitive than other MSCs. In this study, we identify novel genes and signal-activating proteins involved in the neural differentiation of hUC-MSCs induced by Low-Intensity Sub-Sonic Vibration (LISSV). RNA sequencing was used to find genes involved in the differentiation process by LISSV. The changes in hUC-MSCs caused by LISSV were confirmed by PLXNA4 overexpression and gene knockdown through small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…To our knowledge, there are no studies in the literature examining the relationship between the mechanisms of phentermine/topiramate and the PLXNA4 gene. However, the PLXNA4 product (plexin A4) is known to function with semaphorin 6A and itself is localized in the hypothalamus [ 8 , 22 ]. Semaphorins function as signaling proteins necessary for development and maintenance of organs and tissues by regulating morphology and motility [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there are no studies in the literature examining the relationship between the mechanisms of phentermine/topiramate and the PLXNA4 gene. However, the PLXNA4 product (plexin A4) is known to function with semaphorin 6A and itself is localized in the hypothalamus [ 8 , 22 ]. Semaphorins function as signaling proteins necessary for development and maintenance of organs and tissues by regulating morphology and motility [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the PLXNA4 product (plexin A4) is known to function with semaphorin 6A and itself is localized in the hypothalamus [ 8 , 22 ]. Semaphorins function as signaling proteins necessary for development and maintenance of organs and tissues by regulating morphology and motility [ 7 , 8 ]. They are in turn regulated by plexin A4 to prevent abnormal mossy fiber projection in the hippocampus [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we found that three of the candidate TE insertions affected the expression of corresponding genes (SVIL, PLXNA4, and NELL2), which are more likely to be the actual targets of positive selection. PLXNA4 is known to play a role as a guide for axons in the development of the nervous system and in the positive regulation of axonogenesis (Cho et al 2022), whereas NELL2 is multifunctional in neural cell growth and is strongly linked to the urinary tract disease (Liu et al 2021).…”
Section: Detection Of Candidate Te Insertions Contributing To Local A...mentioning
confidence: 99%